Religion in an Age of Empire: The Salvation Army and British Imperialism, 1878–1914 - Eason, Andrew Mark (Journal of religious history, 2021)
Debates about the British Empire continue to rage, especially those concerned with its impact on domestic affairs during the Victorian and Edwardian periods. The degree to which empire mattered to average Britons at home has tended to generate polarised responses from historians. Some have sought to downplay its overall significance, whereas others have been prone to argue that its effects on society were widespread. The present article speaks into this debate by examining one notable British organisation — the Salvation Army — which came into being in the second half of the nineteenth century. While a number of scholars have addressed the imperialist implications of Army work in the colonies, much less work has been done to scrutinise the empire's influence on Salvationists within Britain itself. Looking at three characteristics frequently associated with imperialist ideology — militarism, racial othering, and devotion to the monarchy — this article contends that the Salvation Army's relationship to the British Empire was remarkably dynamic and complex during the timeframe under review. Demonstrating that Salvationist thinking and practice could both help and hinder the aims of imperialism, it points to the need for more balanced and nuanced approaches to the study of the empire in the metropole.